What makes community engagement effective?: Lessons from the Eliminate Dengue Program in Queensland Australia. - Pamela A Kolopack; Janet A Parsons; James V Lavery (Public Library of Science (PLoS), 2015)
BACKGROUND:Worldwide, more than 40% of the population is at risk from dengue and recent estimates suggest that up to 390 million dengue infections are acquired every year. The Eliminate Dengue (ED) Program is investigating the use of Wolbachia-infected, transmission-compromised, mosquitoes to reduce dengue transmission. Previous introductions of genetically-modified strategies for dengue vector control have generated controversy internationally by inadequately engaging host communities. Community Engagement (CE) was a key component of the ED Program's initial open release trials in Queensland Australia. Their approach to CE was perceived as effective by the ED team's senior leadership, members of its CE team, and by its funders, but if and why this was the case was unclear. We conducted a qualitative case study of the ED Program's approach to CE to identify and critically examine its components, and to explain whether and how these efforts contributed to the support received by stakeholders. METHODOLOGY/PRINCIPAL FINDINGS:In-depth semi-structured interviews were conducted with 24 participants with a range of experiences and perspectives related to the ED Program's CE activities. Our analytic approach combined techniques of grounded theory and qualitative description. The ED Program's approach to CE reflected four foundational features: 1) enabling conditions; 2) leadership; 3) core commitments and guiding values; and 4) formative social science research. These foundations informed five key operational practices: 1) building the CE team; 2) integrating CE into management practices; 3) discerning the community of stakeholders; 4) establishing and maintaining a presence in the community; and 5) socializing the technology and research strategy. We also demonstrate how these practices contributed to stakeholders' willingness to support the trials. CONCLUSIONS/SIGNIFICANCE:Our case study has identified, and explained the functional relationships among, the critical features of the ED Program's approach to CE. It has also illuminated how these features were meaningful to stakeholders and contributed to garnering support within the host communities for the open-release trials. Our findings reveal how translating ethical intentions into effective action is more socially complex than is currently reflected in the CE literature. Because our case study delineates the critical features of the ED Program's approach to CE, it can serve as a framework for other programs to follow when designing their own strategies. And because the findings outline a theory of change for CE, it can also serve as a starting point for developing an evaluation framework for CE.